Slownik lekarski angielsko-polski - Slomski, Przemyslaw (Warszawa : Panstwowy Zaklad Wydawnictw Lekarskich, 1991)
An up-to-date English/Polish medical dictionary.
Title on added t.p.: English-Polish medical dictionary.
Includes bibliographical references (p. [17]).
Keywords: Medicine -- Dictionaries -- English; English language -- Dictionaries -- Polish